Wireless Coexistence between IEEE 802.11- and IEEE 802.15.4-Based Networks: A Survey. (11th July 2011) - Yang, Dong; Xu, Youzhi; Gidlund, Mikael
Abstract : As more and more wireless devices use the 2.4 GHz radio spectrum, the coexistence of 2.4 GHz wireless devices operating in one place has become a hot topic. With low transmit power, the widely deployed IEEE 802.15.4-based networks are easily interfered with by other 2.4 GHz wireless networks, such as IEEE 802.11. IEEE 802.15.4-based wireless networks have paid great attention to the coexistence between themselves and with other non-IEEE 802.15.4 wireless networks. This problem has been further promoted by two new industry wireless standards, WirelessHART and ISA100, to meet special industry requirements. This paper surveys the studies on the coexistence between IEEE 802.11 and IEEE 802.15.4-based networks following the general analysis method of "question-analysis-solution." Based on the survey study, we discuss about some open research issues and developments in this field.